Positive electrode material and preparation method thereof, positive plate, battery and electric device

By designing the positive electrode material with manganese concentration gradient and radial growth structure, the problem of the existing positive pole materials in terms of multiplier and circulation performance is solved, and the performance of lithium ion batteries has been significantly improved.

CN119340384AInactive Publication Date: 2025-01-21GUANGZHOU AUTOMOBILE GROUP CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411800962.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-01-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

There are differences in the ratio performance and circulation performance of existing cathode materials, which limits the practical application of lithium-ion batteries.

Method used

Using a positive electrode material, it consists of a secondary particle. Each secondary particle includes one particle. The content of manganese elements gradually decreases from inside to the surface. Crystal structure.

Benefits of technology

Through this structural design, the lattice distortion is effectively suppressed in the cycle, the stability of the lattice oxygen is improved, the strain in the process of dehydration is reduced, the structural changes in the long cycle process are enhanced, High and low temperature discharge performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340384A_ABST
    Figure CN119340384A_ABST
Patent Text Reader

Abstract

In order to solve the problem that an existing positive electrode material is poor in rate capability and cycle performance, the invention provides a positive electrode material and a preparation method thereof, a positive plate, a battery and a power utilization device, the positive electrode material comprises secondary particles, each secondary particle comprises primary particles, and the content of manganese element in the primary particles is gradually reduced from inside to surface; crystal grains of the primary particles grow and are arranged along the radial direction and are arranged in a divergent manner; the secondary particles are of spherical polycrystalline structures; the structural general formula of the positive electrode material is Li1 + xMnaMdO2, M is selected from at least two of Co, Al, Ni, Mg, Ti, Zr, B, Y, W, Sr, La, Ta, Mo and Nb, x is greater than 0 and less than 1, and alt is greater than or equal to 0.3 and less than or equal to 1; 1, 0lt; dlt; 1. When the positive electrode material is made into a positive plate and is applied to an electrochemical device, the cycle durability, the high-rate discharge performance, the power performance and the high and low temperature performance of a battery are remarkably improved, and the problem that the overall performance of a battery cell is poor in the prior art is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery positive electrode materials, and in particular relates to a positive electrode material and a preparation method thereof, a positive electrode sheet, a secondary battery and an electrical device. Background Art

[0002] As people's requirements for the driving range of new energy electric vehicles increase, finding lithium-ion batteries with high energy density and high power density has become the focus of researchers, and the positive electrode material is one of the key parts that restrict the specific capacity, energy density and power density of lithium-ion batteries. In actual application, the positive electrode material has the problems of poor rate performance and poor cycle performance, which seriously hinders its actual application. Summary of the invention

[0003] In view of the problem that existing positive electrode materials have poor rate performance and cycle performance, the present invention provides a positive electrode material and a preparation method thereof, a positive electrode sheet, a secondary battery and an electrical device.

[0004] The technical solution adopted by the present invention to solve the above technical problems is as follows: In a first aspect, the present invention provides a positive electrode material, including secondary particles, each of which includes primary particles, and the content of manganese in the primary particles gradually decreases from the inside to the surface; the grains of the primary particles grow and are arranged radially and in a divergent manner; the secondary particles have a spherical polycrystalline structure; The general structural formula of the positive electrode material is Li 1+x Mn a M d O2, wherein M is selected from at least two of Co, Al, Ni, Mg, Ti, Zr, B, Y, W, Sr, La, Ta, Mo, Nb, 0<x<1, 0.3≤a<1, 0 <d<1。

[0005] Optionally, the positive electrode material has the general structural formula of Li 1+x Mn a Co b Ni c A y A' z O2, wherein A and A' are each independently selected from at least one of Al, Mg, Ti, Zr, B, Y, W, Sr, La, Ta, Mo, and Nb, 0<x<1, 0.3≤a<1, 0 <b≤0.5,0<c≤0.5,0<y≤0.05,0<z≤0.03。

[0006] Optionally, the positive electrode material includes Li 1.21 Mn 0.54 Co 0.13 Ni 0.13 B 0.0097W 0.0024 O2、Li 1.17 Mn 0.5 Co 0.17 Ni 0.17 Al 0.005 Ta 0.005 O2、Li 1.19 Mn 0.56 Co 0.12 Ni 0.12 Y 0.003 Nb 0.003 O2、Li 1.21 Mn 0.54 Co 0.13 Ni 0.13 Zr 0.004 W 0.00 2O2 or more.

[0007] Optionally, the valence of A' is greater than the valence of A.

[0008] Optionally, the particle size of the primary particles is 50-400 nm, and the volume average particle size D50 of the secondary particles is 5-15 μm.

[0009] In a second aspect, the present invention further provides a method for preparing the positive electrode material as described in any one of the above, comprising the following steps: Nickel sulfate, cobalt sulfate and manganese sulfate are prepared in a molar ratio of 1:1:(2-20) to prepare a solution 1 with a total metal concentration of 1-4 mol / L; a precipitant solution 2 is prepared at 2-10 mol / L; a complexing agent solution 3 is prepared at 4-20 mol / L; nickel sulfate, cobalt sulfate and manganese sulfate are prepared in a molar ratio of 1:1:(1-6) to prepare a solution 4 with a total metal concentration of 1-4 mol / L; a solution 5 containing A and A' is prepared; the concentration of manganese ions in the solution 4 is less than the concentration of manganese ions in the solution 1; the concentration of the complexing agent solution 3 is greater than the concentration of the precipitant solution 2; Deionized water and protective gas are introduced into the reactor, the solution 1, the precipitant solution 2, and the complexing agent solution 3 are added into the reactor to obtain a reaction solution 1, the pH value of the reaction solution 1 is adjusted to 7-12, and the reaction solution 1 is subjected to a coprecipitation reaction to obtain a nickel-cobalt-manganese carbonate precursor suspension; Adding solution 4 to a reactor containing the nickel-cobalt-manganese carbonate precursor suspension, suspending the introduction of solution 1, regulating the feed amounts of solution 2 and solution 3 to maintain the pH balance of the reaction, and obtaining reaction solution 2, wherein when the molar ratio of Ni, Co, and Mn in the reaction solution 2 is (0-0.5): (0-0.5): (0.4-1), stopping the addition of solution 4, and then adding solution 5 into the reactor through a metering pump until the volume average particle size D50 of the product particles in the reaction solution 2 is 5-15 μm, stopping the reaction, and post-treating the product in the reaction solution 2 to obtain a lithium-rich manganese-based positive electrode precursor; The lithium-containing compound is mixed with the lithium-rich manganese-based positive electrode precursor to obtain a mixture, and the mixture is sintered and then cooled to obtain a positive electrode material.

[0010] Optionally, the reaction temperature of the reaction solution 1 is 40-70° C., and the stirring speed is 300-600 r / min; The reaction temperature of the reaction solution 2 is 40-70° C., and the stirring speed is 300-600 r / min.

[0011] Optionally, the molar ratio of A to A' is (10:1) to (1:3); And / or, the ratio of the sum of the amounts of Ni, Co, and Mn in the lithium-rich manganese-based positive electrode precursor to the sum of the amounts of A and A' is (95-100): (0-5).

[0012] Optionally, the sintering method is to increase the temperature to 300-550°C at a heating rate of 2-5°C / min and keep it warm for 3-6 hours, and then increase the temperature to 700-1000°C at a heating rate of 2-5°C / min and keep it warm for 8-24 hours.

[0013] Optionally, the lithium-containing compound + The ratio of the amount of substance to the total amount of metal ions in the lithium-rich manganese-based positive electrode precursor is (1.0~1.5):1.

[0014] In a third aspect, the present invention provides a positive electrode sheet, comprising a positive electrode current collector and a positive electrode active material layer arranged on at least one side of the positive electrode current collector, wherein the positive electrode active material layer comprises the positive electrode material as described in any one of the above items, or the positive electrode active material layer comprises the positive electrode material prepared by the preparation method of the positive electrode material as described in any one of the above items.

[0015] In a fourth aspect, the present invention provides a battery comprising a negative electrode and a positive electrode sheet as described in any one of the above items.

[0016] In a fifth aspect, the present invention provides an electrical device comprising a battery as described in any one of the above items.

[0017] In the present invention, in the secondary particles composed of primary particles, the content of manganese in the primary particles gradually decreases from the inside to the surface, presenting a concentration gradient structure with manganese-poor surface and manganese-rich inside. The special structural design can effectively inhibit the lattice distortion during the cycle and improve the lattice oxygen stability, inhibit the anisotropic strain generated by the continuous lithium insertion and extraction process, and improve the reversibility of structural changes during long cycles. At the same time, the concentration gradient structure of manganese can effectively alleviate the dissolution of manganese and the release of lattice oxygen during the cycle.

[0018] The grains of primary particles in the positive electrode material grow and arrange radially and are arranged in a divergent manner. They have a radially ordered grain structure, which can inhibit the irreversible phase change caused by structural instability under deep charge state and the crystal / intercrystalline cracks caused by stress accumulation, inhibit the pulverization of secondary particles, promote cycle stability, and alleviate the problem of easy particle breakage and particle pulverization of polycrystalline positive electrodes during the cycle. At the same time, the radial arrangement of grains improves the conductivity of the positive electrode material, reduces the internal lithium diffusion impedance of the positive electrode material, further improves the lithium diffusion and lithium transmission capabilities, and helps to improve the rate discharge performance and high and low temperature discharge performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 is the XRD structure diagram corresponding to the positive electrode material of Example 1; Figure 2 is the SEM surface image corresponding to the positive electrode material of Example 1; Figure 3 is a SEM cross-sectional view corresponding to the positive electrode material of Example 1; Figure 4 This is a 25°C rate discharge performance diagram of a soft-pack battery corresponding to the positive electrode material of Example 1; Figure 5 This is a high and low temperature discharge performance diagram of a soft-pack battery corresponding to the positive electrode material of Example 1; Figure 6 This is the 45°C cycle capacity retention curve of the soft-pack battery corresponding to the positive electrode material of Example 1. DETAILED DESCRIPTION

[0020] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0021] An embodiment of the present invention provides a positive electrode material, including secondary particles, each of which includes primary particles, and the content of manganese in the primary particles gradually decreases from the inside to the surface; the grains of the primary particles grow and arrange radially and are arranged in a divergent manner; the secondary particles have a spherical polycrystalline structure; The general structural formula of the positive electrode material is Li 1+x Mn a M d O2, wherein M is selected from at least two of Co, Al, Ni, Mg, Ti, Zr, B, Y, W, Sr, La, Ta, Mo, Nb, 0<x<1, 0.3≤a<1, 0 <d<1。

[0022] In this embodiment, among the secondary particles composed of primary particles, the primary particle lithium-manganese-rich based positive electrode has a concentration gradient structure, and the manganese content decreases linearly from the inside to the surface. The special structural design helps to enhance the mechanical strength of the particles, inhibit surface recombination and stabilize the surface lattice oxygen, thereby improving the material structure stability and cycle performance during long cycles.

[0023] The grains of primary particles in the positive electrode material grow and arrange radially and are arranged in a divergent manner. They have a radially ordered grain structure, which can inhibit the irreversible phase change caused by structural instability under deep charge state and the crystal / intercrystalline cracks caused by stress accumulation, inhibit the pulverization of secondary particles, promote cycle stability, and alleviate the problem of easy particle breakage and particle pulverization of polycrystalline positive electrodes during the cycle. At the same time, the radial arrangement of grains improves the conductivity of the positive electrode material, reduces the internal lithium diffusion impedance of the positive electrode material, further improves the lithium diffusion and lithium transmission capabilities, and helps to improve the rate discharge performance and high and low temperature discharge performance.

[0024] In one embodiment, the positive electrode material has the general structural formula of Li 1+x Mn a Co b Ni c A y A' z O2, wherein A and A' are each independently selected from at least one of Al, Mg, Ti, Zr, B, Y, W, Sr, La, Ta, Mo, and Nb, 0<x<1, 0.3≤a<1, 0 <b≤0.5,0<c≤0.5,0<y≤0.05,0<z≤0.03。

[0025] In this embodiment, the positive electrode material is doped with A element and A' element to change the surface energy of the crystal plane, inducing the preferential growth of slender primary particles arranged radially along the layered surface, and the crystal axis of the grains is longer in the radial direction and arranged in order. At the same time, the synergistic effect of multi-element doping overcomes the structural defects of the positive electrode material itself, and can improve the electrochemical performance of the positive electrode material from many aspects, and improve the discharge capacity and cycle performance of the positive electrode material.

[0026] At the same time, if transition metal ions are selected as elements A and A', doping and embedding transition metal ions into the positive electrode material can inhibit the dissolution of metal elements in the main structure of the positive electrode material, inhibit the phase transformation and oxygen release behavior of the deeply delithiated structure, and solve the problem of positive electrode structure collapse during long cycles.

[0027] In one embodiment, the positive electrode material includes Li 1.21 Mn 0.54 Co 0.13 Ni 0.13 B 0.0097 W 0.0024 O2、Li 1.17 Mn 0. 5Co 0.17 Ni 0.17 Al 0.005 Ta 0.005 O2、Li 1.19 Mn 0.56 Co 0.12 Ni 0.12 Y 0.003 Nb 0.003 O2、Li 1.21 Mn 0.54 Co 0.13 Ni 0.13 Zr 0.004 W 0.002 O2. By selecting the above positive electrode materials, the prepared pole piece has a higher compaction density, realizing the practical application of high specific energy lithium-rich manganese-based lithium-ion batteries. At the same time, the positive electrode material of this structure helps to improve the overall performance of the battery.

[0028] In one embodiment, the valence of A' is greater than the valence of A. Low-valence A ion doping strengthens the crystal structure, reduces the degree of cation mixing, and improves structural stability by increasing the TM-O bond energy. High-valence A' ion doping optimizes the morphology of primary particles, transforms the original particles into a rod-like structure with a radially arranged structure, and the morphology and orientation of the primary particles improve the overall mechanical strength and effectively inhibit the generation of microcracks. The embodiment using dual doping combines the advantages of two dopants and exhibits excellent performance enhancement effects through the synergistic effect of the doping element and other elements in the positive electrode material.

[0029] In one embodiment, the particle size of the primary particles is 50-400 nm, and the volume average particle size D50 of the secondary particles is 5-15 μm. By selecting the positive electrode material within the above particle size range, the electrode sheet prepared from the positive electrode material has a higher compaction density.

[0030] In a specific embodiment, the particle size of the primary particles includes but is not limited to 50 nm, 70 nm, 90 nm, 110 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm or 400 nm. The volume average particle size D50 of the secondary particles includes but is not limited to 5 μm, 7 μm, 9 μm, 11 μm, 13 μm or 15 μm.

[0031] In a second aspect, an embodiment of the present invention further provides a method for preparing the positive electrode material as described in any one of the above, comprising the following steps: Nickel sulfate, cobalt sulfate and manganese sulfate are prepared in a molar ratio of 1:1:(2~10) to form a solution 1 with a total metal concentration of 1~4 mol / L; a precipitant solution 2 is prepared at 2~10 mol / L; a complexing agent solution 3 is prepared at 4~20 mol / L; nickel sulfate, cobalt sulfate and manganese sulfate are prepared in a molar ratio of 1:1:(1~6) to form a solution 4 with a total metal concentration of 1~4 mol / L; a solution 5 containing A and A' is prepared; the concentration of manganese ions in the solution 4 is less than the concentration of manganese ions in the solution 1; the concentration of the complexing agent solution 3 is greater than the concentration of the precipitant solution 2, so as to control the pH of the reaction solution and provide a growth direction for grain growth. Specifically, the precipitant solution 2 includes at least one of a sodium carbonate solution and a sodium hydroxide solution. The complexing agent solution 3 includes at least one of an ammonia solution and a sodium citrate solution.

[0032] Deionized water and protective gas are introduced into the reactor, and the solution 1, the precipitant solution 2, and the complexing agent solution 3 are sequentially added into the coprecipitation reactor through a metering pump to obtain a reaction solution 1, and the pH value of the reaction solution 1 is adjusted to 7-12, preferably, the pH value of the reaction solution 1 is adjusted to 9-12. The reaction solution 1 is subjected to a coprecipitation reaction to obtain a nickel-cobalt-manganese carbonate precursor suspension. Specifically, the protective gas is nitrogen or argon, and the coprecipitation reaction time is 2-6 hours.

[0033] Add solution 4 to the reactor containing the nickel-cobalt-manganese carbonate precursor suspension, stop introducing solution 1, adjust the feed amount of solution 2 and solution 3 to maintain the reaction pH balance, and obtain reaction solution 2. When the molar ratio of Ni, Co, and Mn in the reaction solution 2 is (0-0.5): (0-0.5): (0.4-1), stop adding solution 4, and then add solution 5 to the reactor until the volume average particle size D50 of the product particles in the reaction solution 2 is 5-15 μm, and then stop the reaction. The product in the reaction solution 2 is post-treated to obtain a lithium-rich manganese-based positive electrode precursor. By maintaining the pH in the reaction solution 2 the same as that in the reaction solution 1, the core-shell boundary structure of the lithium-rich manganese-based positive electrode precursor is prevented.

[0034] The lithium-containing compound is mixed with the lithium-rich manganese-based positive electrode precursor to obtain a mixture, and the mixture is sintered and then cooled to obtain a positive electrode material.

[0035] In this embodiment, the content of manganese sulfate in solution one is lower than the content of manganese sulfate in solution four, so that the positive electrode material after the secondary precipitation presents a concentration gradient structure with poor manganese on the surface and rich manganese inside. By regulating the concentrations of precipitant solution two and complexing agent solution three, a radial growth environment is provided for the grains. By introducing solution five containing A and A', the high-valence A' can regulate the growth direction of the crystal plane during precipitation and sintering. During the sintering process, A and A' can effectively prevent the high-temperature melting growth of the grains, hinder the migration of matrix atoms across the grain boundaries during the lithiation process, and inhibit the coarsening of the grains, so that the radial ordered structure of the precursor is easier to maintain.

[0036] In one embodiment, the reaction temperature of the reaction solution 1 is 40-70° C., and the stirring speed is 300-600 r / min; The reaction temperature of the reaction solution 2 is 40-70° C., and the stirring speed is 300-600 r / min.

[0037] In one embodiment, the molar ratio of A to A' is (10:1) to (1:3).

[0038] The ratio of the sum of the amounts of Ni, Co, and Mn to the sum of the amounts of A and A' in the lithium-rich manganese-based positive electrode precursor is (95-100): (0-5). By controlling the amounts of A and A', the positive electrode material is doped to improve the particle structure and inhibit particle pulverization.

[0039] In one embodiment, the sintering method is to increase the temperature to 300-550°C at a heating rate of 2-5°C / min and keep it at that temperature for 3-6 hours, and then increase the temperature to 700-1000°C at a heating rate of 2-5°C / min and keep it at that temperature for 8-24 hours.

[0040] By adjusting the appropriate calcination temperature and time, the radial structure of the lithium-rich manganese-based positive electrode precursor is maintained during the high-temperature calcination process. It has a high degree of crystallinity, and the particles will not coarsen and grow to undergo morphological changes.

[0041] In one embodiment, the lithium-containing compound contains Li + The ratio of the amount of the substance to the total amount of metal ions in the lithium-rich manganese-based positive electrode precursor is (1.0-1.5): 1. Specifically, the lithium-containing compound is selected from at least one of lithium hydroxide, lithium carbonate, and lithium acetate.

[0042] In a third aspect, an embodiment of the present invention provides a positive electrode sheet, comprising a positive electrode current collector and a positive electrode active material layer arranged on at least one side of the positive electrode current collector, wherein the positive electrode active material layer comprises the positive electrode material as described in any one of the above items, or the positive electrode active material layer comprises the positive electrode material prepared by the preparation method of the positive electrode material as described in any one of the above items.

[0043] In a fourth aspect, an embodiment of the present invention provides a battery, comprising a negative electrode and a positive electrode sheet as described in any one of the above items.

[0044] In a fifth aspect, an embodiment of the present invention provides an electrical device, comprising a battery as described in any one of the above items.

[0045] The present invention is further described below by way of examples.

[0046] Example 1 This embodiment is used to illustrate the positive electrode material and the preparation method thereof disclosed in the present invention. The preparation of the positive electrode material includes the following steps: S1. Prepare nickel sulfate, cobalt sulfate and manganese sulfate compounds in a molar ratio of 1:1:5 to prepare a solution with a total metal concentration of 2 mol / L; prepare 4 mol / L sodium carbonate solution as a precipitant solution 2, use 10 mol / L ammonia solution as a complexing agent solution 3, prepare nickel sulfate, cobalt sulfate and manganese sulfate compounds in a molar ratio of 1:1:2 to prepare a solution with a total metal concentration of 2 mol / L; prepare a solution containing B and W, wherein B 3+ With W 6+ The molar ratio is 4:1, the element doping amount is based on the total molar amount of the lithium-rich manganese-based positive electrode precursor, and the molar ratio of (Ni+Co+Mn) / (B+W) in the precursor is 98.8:1.2.

[0047] S2. Deionized water was prepared as the reaction liquid and introduced into the reactor. During the reaction, high-purity N2 was continuously introduced to remove oxygen in the solution. The temperature of the reactor was set to 50°C and the stirring speed was 300 r / min. The above solution 1, precipitant solution 2 and complexing agent solution 3 were sequentially added into the reactor through a metering pump. The pH value of the reaction system was adjusted and controlled to 10.6. The coprecipitation reaction was carried out for 3.5 hours to obtain a nickel-cobalt-manganese carbonate precursor suspension.

[0048] S3. Add the above solution 4 to the reactor through a metering pump, stop adding solution 1, and fine-tune the feeding amount of sodium carbonate and ammonia water to maintain the pH balance of the reaction. When the transition metal molar ratio in the reactor reaches Ni:Co:Mn=0.13:0.13:0.54, stop adding solution 4; then add the above solution 5 to the reactor through a metering pump, continue to react until D50 reaches 7.0μm, then stop the reaction. Wash, filter, dry, sieve, and remove impurities from the reactor slurry to obtain a lithium-rich manganese-based positive electrode precursor.

[0049] S4. Lithium reaction: Li2CO3 is fully mixed with the lithium-rich manganese-based positive electrode precursor, where Li + The molar ratio of the amount of the lithium-rich manganese-based precursor to the total metal ions is 1.2:1, the temperature is raised to 500°C at a rate of 5°C / min and kept at this temperature for 5 hours, the temperature is raised to 900°C at a rate of 3°C / min and kept at this temperature for 12 hours, and the positive electrode material Li is obtained by cooling. 1.21 Mn 0.54 Co 0.13 Ni 0.13 B 0.0097 W 0.0024 O2.

[0050] Example 2 This embodiment is used to illustrate the positive electrode material and the preparation method thereof disclosed in the present invention. The preparation of the positive electrode material includes the following steps: S1. Prepare nickel sulfate, cobalt sulfate and manganese sulfate compounds in a molar ratio of 1:1:4 to prepare a solution 1 with a total metal concentration of 2.5 mol / L; prepare 4 mol / L sodium carbonate solution as a precipitant solution 2, use 8 mol / L ammonia solution as a complexing agent solution 3, prepare nickel sulfate, cobalt sulfate and manganese sulfate compounds in a molar ratio of 1:1:2 to prepare a solution 4 with a total metal concentration of 2 mol / L; prepare a solution 5 containing Al and Ta, wherein Al 3+ With Ta 5+ The molar ratio is 1:1, the element doping amount is based on the total molar amount of the lithium-rich manganese-based positive electrode precursor, and the molar ratio of (Ni+Co+Mn) / (Al+Ta) in the precursor is 99.0:1.0.

[0051] S2. Deionized water was prepared as the reaction liquid and introduced into the reactor. During the reaction, high-purity N2 was continuously introduced to remove oxygen in the solution. The temperature of the reactor was set to 55°C and the stirring speed was 360 r / min. The above solution 1, precipitant solution 2 and complexing agent solution 3 were added to the reactor respectively. The pH value of the reaction system was adjusted and controlled to 11.0. The coprecipitation reaction was carried out for 3 hours to obtain a nickel-cobalt-manganese carbonate precursor suspension.

[0052] S3. Add the above solution 4 into the reactor through a metering pump, stop adding solution 1, and fine-tune the feeding amount of sodium carbonate and ammonia water to maintain the pH balance of the reaction. When the transition metal molar ratio in the reactor reaches Ni:Co:Mn=0.17:0.17:0.50, stop adding solution 4; then add the above solution 5 into the reactor through a metering pump, continue to react until D50 reaches 7.5μm, then stop the reaction. Wash, filter, dry, sieve, and remove impurities from the reactor slurry to obtain a lithium-rich manganese-based positive electrode precursor.

[0053] S4. Lithium reaction: Li2CO3 is fully mixed with the lithium-rich manganese-based positive electrode precursor, where Li + The molar ratio of the amount of the lithium-rich manganese-based precursor to the total metal ions is 1.16:1, the temperature is raised to 450°C at a heating rate of 3°C / min and kept warm for 5 hours, the temperature is raised to 920°C at a heating rate of 3°C / min and kept warm for 10 hours, and the positive electrode material Li is obtained by cooling. 1.17 Mn 0.5 Co 0.17 Ni 0.17 Al 0.005 Ta 0.005 O2.

[0054] Example 3 This embodiment is used to illustrate the positive electrode material and the preparation method thereof disclosed in the present invention. The preparation of the positive electrode material includes the following steps: S1. Prepare nickel sulfate, cobalt sulfate and manganese sulfate compounds in a molar ratio of 1:1:6 to prepare a solution with a total metal concentration of 2 mol / L; prepare 3 mol / L sodium carbonate solution as a precipitant solution 2, use 8 mol / L ammonia solution as a complexing agent solution 3, prepare nickel sulfate, cobalt sulfate and manganese sulfate compounds in a molar ratio of 1:1:2 to prepare a solution with a total metal concentration of 2 mol / L; prepare a solution containing Y and Nb, wherein Y 3+ With Nb 5+ The molar ratio is 1:1, the element doping amount is based on the total molar amount of the lithium-rich manganese-based positive electrode precursor, and the molar ratio of (Ni+Co+Mn) / (Y+Nb) in the precursor is 99.4:0.6.

[0055] S2. Deionized water was prepared as the reaction liquid and introduced into the reactor. During the reaction, high-purity N2 was continuously introduced to remove oxygen in the solution. The temperature of the reactor was set to 60°C and the stirring speed was 400r / min. The above solution 1, precipitant solution 2 and complexing agent solution 3 were added to the reactor respectively. The pH value of the reaction system was adjusted and controlled to 10.8. The coprecipitation reaction was carried out for 4.5 hours to obtain a nickel-cobalt-manganese carbonate precursor suspension.

[0056] S3. Add the above solution 4 into the reactor through a metering pump, stop adding solution 1, and fine-tune the feeding amount of sodium carbonate and ammonia water to maintain the pH balance of the reaction. When the transition metal molar ratio in the reactor reaches Ni:Co:Mn=0.12:0.12:0.56, stop adding solution 4; then add the above solution 5 into the reactor through a metering pump, continue to react until D50 reaches 6.5μm, then stop the reaction. Wash, filter, dry, sieve, and remove impurities from the reactor slurry to obtain a lithium-rich manganese-based positive electrode precursor.

[0057] S4. Lithium reaction: Li2CO3 is fully mixed with the lithium-rich manganese-based positive electrode precursor, where Li + The molar ratio of the amount of the lithium-rich manganese-based precursor to the total metal ions is 1.18:1, the temperature is raised to 500°C at a rate of 3°C / min and kept for 4 hours, the temperature is raised to 950°C at a rate of 3°C / min and kept for 15 hours, and the positive electrode material Li is obtained by cooling. 1.19 Mn 0.56 Co 0.12 Ni 0.12 Y 0.003 Nb 0.003 O2.

[0058] Example 4 This embodiment is used to illustrate the positive electrode material and the preparation method thereof disclosed in the present invention. The preparation of the positive electrode material includes the following steps: S1. Prepare nickel sulfate, cobalt sulfate and manganese sulfate compounds in a molar ratio of 1:1:5 to prepare a solution 1 with a total metal concentration of 2 mol / L; prepare 4 mol / L sodium carbonate solution as a precipitant solution 2, use 8 mol / L ammonia solution as a complexing agent solution 3, prepare nickel sulfate, cobalt sulfate and manganese sulfate compounds in a molar ratio of 1:1:3 to prepare a solution 4 with a total metal concentration of 2 mol / L, prepare a solution 5 containing Ti and W, wherein Zr 4+ With W 6+ The molar ratio is 2:1, the element doping amount is based on the total molar amount of the lithium-rich manganese-based positive electrode precursor, and the molar ratio of (Ni+Co+Mn) / (Zr+W) in the precursor is 99.4:0.6.

[0059] S2. Deionized water was prepared as the reaction liquid and introduced into the reactor. During the reaction, high-purity N2 was continuously introduced to remove oxygen in the solution. The temperature of the reactor was set to 50°C and the stirring speed was 320 r / min. The above solution 1, precipitant solution 2 and complexing agent solution 3 were added to the reactor respectively. The pH value of the reaction system was adjusted and controlled to 10.2. The coprecipitation reaction was carried out for 4 hours to obtain a nickel-cobalt-manganese carbonate precursor suspension.

[0060] S3. Add the above solution 4 into the reactor through a metering pump, stop adding solution 1, and fine-tune the feeding amount of sodium carbonate and ammonia water to maintain the pH balance of the reaction. When the transition metal molar ratio in the reactor reaches Ni:Co:Mn=0.13:0.13:0.54, stop adding solution 4; then add the above solution 5 into the reactor through a metering pump, continue to react until D50 reaches 7.5μm, then stop the reaction. Wash, filter, dry, sieve, and remove impurities from the reactor slurry to obtain a lithium-rich manganese-based positive electrode precursor.

[0061] S4. Lithium reaction: Li2CO3 is fully mixed with the lithium-rich manganese-based positive electrode precursor, where Li + The molar ratio of the amount of the lithium-rich manganese-based precursor to the total metal ions is 1.2:1, the temperature is raised to 500°C at a heating rate of 5°C / min and kept for 5 hours, the temperature is raised to 960°C at a heating rate of 3°C / min and kept for 12 hours, and the positive electrode material Li is obtained by cooling. 1.21 Mn 0.54 Co 0.13 Ni 0.13 Zr 0.004 W 0.002 O2.

[0062] Example 5 This example is used to compare and illustrate the positive electrode material and preparation method thereof disclosed in the present invention, and includes most of the operation steps in Example 1, except that: in step S3, solution 5 is not added to obtain the positive electrode material Li 1.2 Mn 0.54 Co 0.13 Ni 0.13 O2.

[0063] Example 6

[0064] This embodiment is used to compare and illustrate the positive electrode material and the preparation method thereof disclosed in the present invention, and includes most of the operating steps in Example 1, except that: in step S1, nickel sulfate, cobalt sulfate and manganese sulfate compounds are configured in a molar ratio of 1:1:10 to form a solution 1 with a total metal concentration of 4 mol / L; 10 mol / L sodium carbonate solution is configured as a precipitant solution 2, 20 mol / L ammonia solution is used as a complexing agent solution 3, and nickel sulfate, cobalt sulfate and manganese sulfate compounds are configured in a molar ratio of 1:1:6 to form a solution 4 with a total metal concentration of 4 mol / L.

[0065] Obtaining positive electrode material Li 1.29 Mn 0.58 Co 0.07 Ni 0.07 B 0.0097 W 0.0024 O2.

[0066] Example 7 This embodiment is used to compare and illustrate the positive electrode material and the preparation method thereof disclosed in the present invention, and includes most of the operating steps in Example 1, except that: in step S1, nickel sulfate, cobalt sulfate and manganese sulfate compounds are configured in a molar ratio of 1:1:2 to form a solution 1 with a total metal concentration of 1 mol / L; 2 mol / L sodium carbonate solution is configured as a precipitant solution 2, 4 mol / L ammonia solution is used as a complexing agent solution 3, and nickel sulfate, cobalt sulfate and manganese sulfate compounds are configured in a molar ratio of 1:1:1 to form a solution 4 with a total metal concentration of 1 mol / L.

[0067] Obtaining positive electrode material Li 1.139 Mn 0.375 Co 0.25 Ni 0.25 B 0.0097 W 0.0024 O2.

[0068] Example 8 This example is used to compare and illustrate the positive electrode material and the preparation method thereof disclosed in the present invention, and includes most of the operation steps in Example 1, except that: Solution 5 contains B and Y.

[0069] Obtaining positive electrode material Li 1.21 Mn 0.54 Co 0.13 Ni 0.13 B 0.0097 Y 0.00024 O2.

[0070] Example 9 This example is used to compare and illustrate the positive electrode material and the preparation method thereof disclosed in the present invention, and includes most of the operation steps in Example 1, except that: Solution 5 contains W and Nb.

[0071] Obtaining positive electrode material Li 1.21 Mn 0.54 Co 0.13 Ni 0.13 Nb 0.003 W 0.0002 O2.

[0072] Comparative Example 1 Comparative Example 1 is used to compare and illustrate the positive electrode material and the preparation method thereof disclosed in the present invention, including most of the operating steps in Example 1, except that: the molar ratio of nickel sulfate, cobalt sulfate and manganese sulfate compounds in solution one to lithium is 1:1:4.154, the concentration of sodium carbonate solution in solution two is 5 mol / L, the concentration of ammonia solution in solution three is 2 mol / L, and step S3 is not included.

[0073] Obtaining positive electrode material Li 1.21 Mn 0.54 Co 0.13 Ni 0.13 B 0.0097 W 0.0024 O2.

[0074] Comparative Example 2 Comparative Example 2 is used to compare and illustrate the positive electrode material and the preparation method thereof disclosed in the present invention, including most of the operating steps in Example 1, the difference being that: Solution 4, precipitant solution 2 and complexing agent solution 3 are added in step S2; Solution 1, solution 5, solution 2 and complexing agent solution 3 are added in step S3.

[0075] Obtaining positive electrode material Li 1.21 Mn 0.54 Co 0.13 Ni 0.13 B 0.0097 W 0.0024 O2.

[0076] Comparative Example 3 Comparative Example 3 is used to compare and illustrate the positive electrode material and the preparation method thereof disclosed in the present invention, including most of the operating steps in Example 1, except that: in step S3, solution one, solution five, solution two and complexing agent solution three are added, wherein the molar ratio of nickel sulfate, cobalt sulfate and manganese sulfate compounds in solution one to lithium is 1:1:4.154.

[0077] Obtaining positive electrode material Li 1.21 Mn 0.54 Co 0.13 Ni 0.13 B 0.0097 W 0.0024 O2.

[0078] Performance Testing Button cell: The positive electrode materials, conductive agent and PVDF of the above-mentioned embodiment and comparative example are weighed and mixed uniformly in a mass ratio of 94:3:3, and dispersed with N-methylpyrrolidone (NMP) solvent to form a slurry; the slurry is uniformly coated on the surface of an aluminum foil and dried at 80°C for 12 hours to obtain a positive electrode sheet. The dried positive electrode sheet is rolled and cut into discs and placed in a glove box for standby use. The above-prepared disc is used as the positive electrode, metallic lithium as the negative electrode, Celgard 2400 (microporous polypropylene membrane) as the diaphragm, and 1 mol / L LiPF6 (FEC:DMC=2:8) as the electrolyte to assemble into a 2032-type button cell. The assembly of the lithium-ion battery must be carried out in a glove box with argon as the protective gas.

[0079] Soft-pack battery: The positive electrode material prepared in the embodiment and comparative example is used as the positive electrode, artificial graphite is used as the negative electrode, commercial electrolyte and separator are used, and the soft-pack battery cell is assembled on the lithium-ion battery production line, wherein the positive electrode sheet includes: the positive electrode material, the conductive agent (conductive carbon black + carbon nanotubes, the mass ratio is 1.5:0.5) and the binder PVDF are uniformly mixed in a mass ratio of 96.5:2:1.5, and the solvent is N-methylpyrrolidone NMP. After stirring evenly to obtain the slurry, it is coated on the aluminum foil current collector, and the positive electrode current collector is 12μm aluminum foil. The pole piece is rolled and pressed into sheets after high-temperature baking, and cut into positive electrode sheets for standby use.

[0080] The negative electrode sheet includes: artificial graphite, conductive agent, sodium carboxymethyl cellulose CMC and binder SBR are uniformly mixed in a mass ratio of 95.5:1.5:1.2:1.8, and the solvent is deionized water. After stirring evenly to obtain a slurry, it is coated on the copper foil current collector, and the negative electrode current collector is 6μm copper foil; and cut into negative electrode sheets for use. The electrolyte standard is 1mol / L LiPF6 (fluoroethylene carbonate FEC: methyl trifluoroethyl carbonate FEMC: 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether TTE=3:5:2) + additives; the diaphragm is a 7+3μm mixed diaphragm (substrate + PVDF & ceramic mixed coating).

[0081] Preparation of lithium-ion soft-pack batteries: stack the positive electrode sheets, isolation films, and negative electrode sheets prepared above in order, and obtain bare cells without liquid injection through a stacking process, wherein the isolation film is located between the positive and negative electrode sheets to play the role of isolation and subsequent transmission of lithium ions; heat-seal the bare cells in an aluminum-plastic film shell, and then inject the electrolyte into the bare cells with a moisture value of <200ppm after baking, and obtain lithium-ion soft-pack batteries through vacuum packaging, hot and cold pressing shaping, formation, shaping, and sorting.

[0082] 1. The button cells and soft pack cells prepared in the above examples and comparative examples were subjected to the following performance tests: 1. Power-off test example: The button cells of the embodiment and the comparative example were subjected to charge and discharge performance tests at a temperature of 25±1°C to test the charge and discharge capacity and charge and discharge efficiency of the button cells under different schemes. The test process is as follows: (1). Activate button cell for 24 hours; (2) 0.1C constant current charging to the upper limit voltage (4.55V) and then constant voltage charging, with a cut-off current of 0.05C; (3) Let stand for 10 minutes; (4). 0.1C constant current discharge to 2.0V, rest for 10 minutes; (5) Calculate the first discharge capacity in grams.

[0083] The discharge capacity in grams of the positive electrode materials of each embodiment and comparative example can be obtained by calculation, and the statistical results are shown in Table 1.

[0084] 2. Lithium ion diffusion coefficient of button battery: The diffusion coefficient of lithium ions (D Li + ).

[0085] The button cells of the embodiment and the comparative example were tested at a temperature of 25±1°C. The testing process was as follows: (1). Activate button cell for 24 hours; (2) 0.1C constant current charging to the upper limit voltage (4.55V) and then constant voltage charging, with a cut-off current of 0.05C; (3) Let stand for 10 minutes; (4). 0.1C constant current discharge for 15 minutes; (5) Let stand for 15 minutes; (6) Repeat steps 4-5 until the discharge process is completed.

[0086] The above test method is used to calculate the diffusion coefficient of the positive electrode material, focusing on four voltage data: the voltage V0 before pulse discharge; the instantaneous voltage V1 of constant current discharge (pulse instantaneous discharge), the difference between V0 and V1 mainly corresponds to the influence of the ohmic impedance and charge transfer impedance inside the battery on the voltage change; the voltage V2 at the end of constant current discharge, corresponding to Li + The voltage change caused by diffusion into the cathode material; the voltage V3 at the end of static state corresponds to Li + Diffusion occurs inside the active material, and finally a steady-state voltage change of the active material is achieved. Based on the above data and combined with Fick's second law, the following formula is used to calculate Li + Diffusion coefficient Ds in lithium-ion batteries.

[0087] Ds=(4 / πt)(Rs / 3) 2 (△Vs / △Vt) 2 ; Here Rs is the radius of the spherical particle, t is the duration of the discharge pulse, △Vs=V0-V3; △Vt=V1-V2.

[0088] 3. Soft pack battery rate performance test: The soft-pack batteries of the embodiment and the comparative example were subjected to rate performance tests at a temperature of 25±1° C. The test process is as follows: (1) Capacity test was performed by 1.0C / 1.0C cycle three times in 25±1℃ environment; (2) 1C discharge to the lower limit voltage (2.5V), and let stand for 30 minutes; (3) 1C constant current charging to the upper limit voltage (4.5V) and then constant voltage charging, cut-off current 0.05C, and stand for 30 minutes; (4).nC discharge to the lower limit voltage, where nC = 0.33C / 1C / 2C / 4C / 8C; (5) Repeat steps 3 to 4 to complete the discharge steps of all rates.

[0089] The rate performance of each battery was obtained through calculation (rate capacity retention rate = 8C discharge capacity / 0.33C capacity). The results are shown in Table 1.

[0090] 4. High and low temperature performance test of soft pack battery The soft-pack batteries of the embodiment and the comparative example were subjected to high and low temperature performance tests at a temperature of 25±1°C. The test process is as follows: (1) Stand at 25±1℃ for 30min; (2). 1C discharge to the lower limit voltage; let stand for 30 minutes; (3) Charge at 1C to the upper voltage limit, cut-off current 0.05C, and let stand for 30 minutes; (4) In a constant temperature box, discharge at 1C to the lower limit voltage after standing for 2 hours at different temperatures (temperatures are as follows); Repeat steps 3 to 4 until all temperature discharge tests are completed; Discharge temperature: 25℃ / 45℃ / 0℃ / -20℃; Discharge cut-off voltage: 2.5V, 0℃≤T≤45℃; 2.0V, -20℃ <T<0℃。

[0091] 5. Soft pack battery 25℃ cycle capacity test The soft-pack batteries of the embodiment and the comparative example were subjected to a cycle capacity test at a temperature of 25±1° C. with a voltage range of 2.5-4.5 V. The test process included: (1) The battery cell is placed in an environment of 25℃±1℃ for 60 minutes; (2) 1C discharge to the lower limit voltage, and let stand for 30 minutes; (3) Charge at 1C to the upper limit voltage, cut off at 0.05C; let stand for 30 minutes; (4). 1C discharge to the lower limit voltage; let stand for 30 minutes; (5) Charge at 1C to the upper limit voltage, cut off at 0.05C, and let stand for 30 minutes; Repeat steps 4 and 5 for n rounds.

[0092] After 1C / 1C and n cycles (n≤5000), the cycle capacity retention rate of each battery was calculated, where the first cycle test capacity was recorded as A1, the test capacity after n cycles was recorded as An, and the capacity retention rate = An / A1×100%. The capacity retention rate results when n=1500 are shown in Table 1.

[0093] 6. Soft pack battery 45℃ cycle capacity test The soft-pack batteries of the embodiment and the comparative example were subjected to a cycle capacity test at a temperature of 45±1°C and a voltage range of 2.5-4.5V. The test process included: (1) The battery cell is placed at 45℃±1℃ for 60 minutes; (2) 1C discharge to the lower limit voltage, and let stand for 30 minutes; (3) Charge at 1C to the upper limit voltage, cut off at 0.05C; let stand for 30 minutes; (4). 1C discharge to the lower limit voltage; let stand for 30 minutes; (5) Charge at 1C to the upper limit voltage, cut off at 0.05C, and let stand for 30 minutes; Repeat steps 4 and 5 for n rounds.

[0094] After 1C / 1C and n cycles (n≤5000), the cycle capacity retention rate of each battery was calculated, where the first cycle test capacity was recorded as A1, the test capacity after n cycles was recorded as An, and the capacity retention rate = An / A1×100%. The capacity retention rate results when n=700 are shown in Table 1.

[0095] 7. DSC test of soft pack battery: The soft-pack battery cell was fully charged to 4.5V at a rate of 1C, and disassembled in a glove box filled with argon to recover the positive electrode, and the electrode was rinsed with dimethyl carbonate (DMC) and dried. The positive electrode and the electrolyte were placed together in the high-pressure crucible of the thermal analysis instrument, and 1 mol / L LiPF6 (EC:DMC:DMC=1:1:1) was used as the electrolyte, where the positive electrode and the electrolyte were added according to 1mg:0.55μL. The thermal analysis test temperature range was 25-400℃, and the heating rate was 5℃ / min. The test results are shown in Table 1.

[0096] Table 1

[0097] Depend on Figure 1 The XRD characterization shows that the sample has obvious diffraction peaks and the diffraction peak intensity is high, indicating that the prepared sample has good crystallinity. The main characteristic diffraction peaks in the XRD spectrum correspond to The weaker diffraction peak between 20 and 25 degrees is due to the L2MnO3 cathode with C2 / m space group.

[0098] Depend on Figure 2 The SEM surface image shows that the secondary particles are spherical polycrystalline. Figure 3 From the characterization of the SEM cross-sectional image, it can be seen that the grains of the primary particles in the positive electrode material obtained in Example 1 grow and arrange along the radial direction and are arranged in a divergent manner.

[0099] Depend on Figure 4~Figure 6 The electrical performance test shows that the soft-pack battery composed of this positive electrode material has good rate discharge performance, good high and low temperature discharge performance, and its capacity retention rate is above 95% during the cycle performance test.

[0100] The positive electrode material obtained in Comparative Example 1 cannot provide a growth direction for the growth of the grains because the concentration of ammonia water is lower than that of the sodium carbonate solution, and the primary grains of the positive electrode material obtained are not arranged in radial growth. In Comparative Example 2, solution four with a lower metal ion concentration was first added, and then solution one was added, so that the positive electrode material obtained had a concentration gradient structure with surface manganese-rich and internal manganese-poor. In Comparative Example 3, solution one was added twice, so that the concentration of manganese in the positive electrode material remained unchanged, and the primary grains grew and arranged radially. The manganese element in the positive electrode material in Examples 1 to 4 has a concentration gradient structure and the positive electrode material is doped with A and A' elements, and the grains of the primary particles grow and arrange radially, and Example 5 is not doped with A and A' elements. It can be seen from the test results of Examples 1 to 5 and Comparative Examples 1 to 3 in Table 1 that the internal lithium diffusion impedance of the positive electrode material of Examples 1 to 4 is reduced, and the lithium ion diffusion coefficient is increased, which helps to improve the rate discharge performance and high and low temperature discharge performance of the battery. And the first discharge capacity, first discharge efficiency, tap density and cycle performance of the battery are obviously due to Comparative Example 1.

[0101] It can be seen from the test results of Examples 1 to 4 and Comparative Examples 2 and 3 that when the content of manganese in the particles follows the law of linear decrease from the inside to the surface, its high safety performance and long cycle life capacity retention rate are significantly improved. It can be seen from the test results of Examples 1 and 5 that when the positive electrode material is not doped with A and A' elements, the safety performance and long cycle life capacity retention rate are lower than those in Example 1, and the DSC decomposition temperature is lower than that in Example 1, and the DSC heat release is higher than that in Example 1. The lower decomposition temperature of the positive electrode material and the excessive heat released are easy to cause the battery temperature to rise, thereby affecting the safety and service life of the battery, which further proves that doping with A and A' elements can inhibit the phase transition and oxygen release behavior of the deep delithiation structure.

[0102] It can be seen from the test results of Examples 1, 6, and 7 that when the total metal concentration of Solution 1 and Solution 4 and the molar ratio of manganese sulfate therein change, the content of each metal element in the positive electrode material changes, resulting in changes in its first discharge gram capacity, tap density, and lithium ion diffusion coefficient.

[0103] From the test results of Examples 1, 8, and 9, it can be seen that when the doping elements are all high-valent elements, the discharge gram capacity of the positive electrode material is suppressed, and when a high-valent metal is used, the doping amount will be too high, and the excessive doping amount suppresses the discharge gram capacity; the safety performance and long cycle capacity retention rate are improved, and the stability of the material is improved. When the doping elements are all low-valent elements, the discharge gram capacity of the positive electrode material is normal, the lithium ion diffusion rate of the material, the rate discharge performance of the battery cell, and the low-temperature discharge performance are slightly worse, and the effect of the low-valent element on regulating the radial growth structure is slightly worse.

[0104] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A positive electrode material, characterized in that: The invention comprises secondary particles, each of which comprises primary particles, and the content of manganese in the primary particles gradually decreases from the inside to the surface; the crystal grains of the primary particles grow and are arranged radially and in a divergent shape, and the secondary particles have a spherical polycrystalline structure; The general structural formula of the positive electrode material is Li 1+x Mn a M d O2, wherein M is selected from at least two of Co, Al, Ni, Mg, Ti, Zr, B, Y, W, Sr, La, Ta, Mo, Nb, 0<x<1, 0.3≤a<1, 0 <d<1。 2. The positive electrode material according to claim 1, characterized in that The general structural formula of the positive electrode material is Li 1+ x Mn a Co b Ni c A y A' z O2, wherein A and A' are each independently selected from at least one of Al, Mg, Ti, Zr, B, Y, W, Sr, La, Ta, Mo, and Nb, 0<x<1, 0.3≤a<1, 0 <b≤0.5,0<c≤0.5,0<y≤0.05,0<z≤0.03。 3. The positive electrode material according to claim 2, characterized in that The positive electrode material includes Li 1.21 Mn 0.54 Co 0.13 Ni 0.13 B 0.0097 W 0.0024 O2、Li 1.17 Mn 0.5 Co 0.17 Ni 0.17 Al 0.005 Ta 0.005 O2、Li 1.19 Mn 0.56 Co 0.12 Ni 0.12 Y 0.003 Nb 0.00 3O2、Li 1.21 Mn 0.54 Co 0.13 Ni 0.13 Zr 0.004 W 0.002 One or more of O2.

4. The positive electrode material according to claim 2, characterized in that The valence of A' is greater than the valence of A.

5. The positive electrode material according to claim 1, characterized in that The particle size of the primary particles is 50-400 nm, and the volume average particle size D50 of the secondary particles is 5-15 μm.

6. The method for preparing a positive electrode material according to any one of claims 1 to 5, characterized in that: The following steps are involved: Nickel sulfate, cobalt sulfate and manganese sulfate are prepared in a molar ratio of 1:1:(2-10) to prepare a solution 1 with a total metal concentration of 1-4 mol / L; a precipitant solution 2 is prepared at 2-10 mol / L; a 4-20 mol / L ammonia solution is prepared as a complexing agent solution 3; nickel sulfate, cobalt sulfate and manganese sulfate are prepared in a molar ratio of 1:1:(1-6) to prepare a solution 4 with a total metal concentration of 1-4 mol / L; a solution 5 containing A and A' is prepared; the concentration of manganese ions in the solution 4 is less than the concentration of manganese ions in the solution 1; the concentration of the complexing agent solution 3 is greater than the concentration of the precipitant solution 2; Deionized water and protective gas are introduced into the reactor, the solution 1, the precipitant solution 2, and the complexing agent solution 3 are added into the reactor to obtain a reaction solution 1, the pH value of the reaction solution 1 is adjusted to 7-12, and the reaction solution 1 is subjected to a coprecipitation reaction to obtain a nickel-cobalt-manganese carbonate precursor suspension; Adding solution 4 to a reactor containing the nickel-cobalt-manganese carbonate precursor suspension, suspending the introduction of solution 1, regulating the feed amounts of solution 2 and solution 3 to maintain the pH balance of the reaction, and obtaining reaction solution 2, wherein when the molar ratio of Ni, Co, and Mn in the reaction solution 2 is (0-0.5): (0-0.5): (0.4-1), stopping the addition of solution 4, and then adding solution 5 to the reactor until the volume average particle size D50 of the product particles in the reaction solution 2 is 5-15 μm, stopping the reaction, and post-treating the product in the reaction solution 2 to obtain a lithium-rich manganese-based positive electrode precursor; The lithium-containing compound is mixed with the lithium-rich manganese-based positive electrode precursor to obtain a mixture, and the mixture is sintered and then cooled to obtain a positive electrode material.

7. The method for preparing the positive electrode material according to claim 6, characterized in that: The reaction temperature of the reaction solution 1 is 40-70°C, and the stirring speed is 300-600r / min; The reaction temperature of the reaction solution 2 is 40-70° C., and the stirring speed is 300-600 r / min.

8. The method for preparing the positive electrode material according to claim 6, characterized in that: The molar ratio of A to A' is (10:1) to (1:3); And / or, the ratio of the sum of the amounts of Ni, Co, and Mn in the lithium-rich manganese-based positive electrode precursor to the sum of the amounts of A and A' is (95-100): (0-5).

9. The method for preparing the positive electrode material according to claim 6, characterized in that: The sintering method comprises heating the temperature to 300-550° C. at a heating rate of 2-5° C. / min and keeping the temperature for 3-6 hours, and then heating the temperature to 700-1000° C. at a heating rate of 2-5° C. / min and keeping the temperature for 8-24 hours.

10. The method for preparing the positive electrode material according to claim 6, characterized in that: The lithium-containing compound contains Li + The ratio of the amount of substance to the total amount of metal ions in the lithium-rich manganese-based positive electrode precursor is (1.0~1.5):

1.

11. A positive electrode sheet, characterized in that: It comprises a positive electrode current collector and a positive electrode active material layer arranged on at least one side of the positive electrode current collector, wherein the positive electrode active material layer comprises the positive electrode material according to any one of claims 1 to 5, or the positive electrode active material layer comprises the positive electrode material prepared by the preparation method of the positive electrode material according to any one of claims 6 to 10.

12. A battery, characterized in that: It comprises a negative electrode and the positive electrode sheet according to claim 11.

13. An electrical device, characterized in that: Comprising the battery as claimed in claim 12.

Citation Information

Patent Citations

  • Lithium-manganese-aluminum oxygen anode material and preparation method thereof

    CN102683667A

  • Lithium nickel manganese oxide material precursor and preparation method thereof, lithium nickel manganese oxide material and preparation method thereof, and lithium ion battery

    CN103000876A

  • Lithium manganese nickel oxide cathode material having nickel manganese concentration gradient and preparation method thereof

    CN105226270A

  • Ternary positive electrode material, method for manufacturing same, and secondary battery using same

    CN115832268A

  • Concentration gradient manganese-rich positive electrode material precursor, preparation method thereof and positive electrode material

    CN118026290A